Streptomyces cameroonensis sp. nov., a Geldanamycin Producer That Promotes Theobroma cacao Growth - Boudjeko, Thaddée (Microbes Environ, 2017)
The taxonomy of an actinobacterial strain, designated JJY4(T), was established using a polyphasic approach. JJY4(T) was isolated from the rhizosphere of Chromolaena odorata in Yaoundé (Cameroon) during a project for the selection of biological control agents. Strain JJY4(T) exhibited antimicrobial activities against bacteria, fungi, and oomycetes. Strain JJY4(T) also exhibited the traits of plant growth-promoting rhizobacteria such as the solubilization of inorganic phosphate, production of siderophores and indole-3-acetic acid, and 1-aminocyclopropane-1-carboxylate deaminase activity. In planta assays performed on cocoa plantlets confirmed that strain JJY4(T) exhibited strong abilities to promote plant growth and protect against Phytophthora megakarya, the main causal agent of cocoa pod rot. The formation of rugose-ornamented spores in spiral spore chains by strain JJY4(T) is a typical feature of members found in the Streptomyces violaceusniger clade and, similar to some members of the clade, strain JJY4(T) produces geldanamycin. A phylogenetic analysis based on 16S rRNA gene sequences confirmed this classification and suggests that strain JJY4(T) be added to the subclade constituted of the type strains Streptomyces malaysiensis DSM 41697(T) and Streptomyces samsunensis DSM 42010(T). However, DNA–DNA relatedness and physiological characteristics allowed for the differentiation of strain JJY4(T) from its closest phylogenetic relatives. Based on these results, strain JJY4(T) (=NRRL B-65369, =NBRC 112705) appears to represent a novel species in the S. violaceusniger clade for which the proposed name is Streptomyces cameroonensis sp. nov.